Improving Financial Report Quality Through Good Governance and Government Accounting Standards in Berau Regency - Siti Munawaroh; Sayugo Adi Purwanto; Djupiansyah Ganie; Caetano Carceres Correia (Pusat Riset dan Inovasi Nasional, 2025)
This research explored the influence of Good Governance and Government Accounting Standards on the quality of financial reports Management Agency and Regional Assets of Berau Regency. Primary data were collected through questionnaires distributed to 60 respondents who were employees of the BPKAD of Berau Regency and used as research samples.